2019
DOI: 10.1111/dom.13684
|View full text |Cite
|
Sign up to set email alerts
|

Decision models of prediabetes populations: A systematic review

Abstract: Aims With evidence supporting the use of preventive interventions for prediabetes populations and the use of novel biomarkers to stratify the risk of progression, there is a need to evaluate their cost‐effectiveness across jurisdictions. Our aim is to summarize and assess the quality and validity of decision models and model‐based economic evaluations of populations with prediabetes, to evaluate their potential use for the assessment of novel prevention strategies and to discuss the knowledge gaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 68 publications
0
27
0
Order By: Relevance
“…Since 2009, in addition to pre-existing diabetes based on fasting plasma glucose (FPG) and 2-h plasma glucose (2-h PG) after an oral glucose tolerance test (OGTT), glycated hemoglobin (HbA1c) has been suggested to be a diagnostic criterion for the detection of diabetes and prediabetes 8 . However, many reports have pointed out diagnostic discrepancies among the three criteria used to categorize hyperglycemia, which could indicate distinct pathophysiological processes and aspects of glucose metabolism different from impaired fasting glucose (IFG) and impaired glucose tolerance (IGT) [8][9][10] . When compared with use of the OGTT, there are several advantages of using FPG and HbA1c values, including greater convenience and fewer day-to-day perturbations (or greater stability), respectively 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Since 2009, in addition to pre-existing diabetes based on fasting plasma glucose (FPG) and 2-h plasma glucose (2-h PG) after an oral glucose tolerance test (OGTT), glycated hemoglobin (HbA1c) has been suggested to be a diagnostic criterion for the detection of diabetes and prediabetes 8 . However, many reports have pointed out diagnostic discrepancies among the three criteria used to categorize hyperglycemia, which could indicate distinct pathophysiological processes and aspects of glucose metabolism different from impaired fasting glucose (IFG) and impaired glucose tolerance (IGT) [8][9][10] . When compared with use of the OGTT, there are several advantages of using FPG and HbA1c values, including greater convenience and fewer day-to-day perturbations (or greater stability), respectively 11 .…”
Section: Introductionmentioning
confidence: 99%
“…We report three estimates of diabetes prevalence in England for 2025 (with 95% CIs where available): 4.39 by PHE,12 4.19 (2.93 to 6.19) by the APHO model,18 25 and 5.46 (5.32 to 5.59) from the QOF trend. We and Leal et al 7 found only minority of articles reported tests of validation. Such checks are vital for Markov chain models given the different data sources used to estimate transition probabilities.…”
Section: Discussionmentioning
confidence: 81%
“…In seven articles these probabilities do vary by age 20–23 25 29 30. In their systematic review of models of the economic impacts of preventive interventions, Leal et al 7 also found the majority of models assumed that ‘the rate of progression to T2D was constant across the entire pre-diabetes population’. They attribute this in part to limitations in the available data, but highlight the ‘stark contrast’ between these simple models and ‘The complexity of risk prediction models for diabetes incidence and the variety of covariates used’ 46 47.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations